FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KETUBAN PECAH DINI PADA IBU BERSALIN DI RSUD LABUANG BAJI MAKASSAR - rohani rohani (Stikes Graha Edukasi Makassar, 2020)
Objective : to determine the relationship between age, parity, pregnancy double to the incidence of premature rupture of membranes in maternity mothers in RSUD Labuang Baji Year 2016 Makassar. Methods: The design of this study used an analytic observational research design using a cross sectional (transversal) approach. total population 795 people, sampling of this research using sampling technique so that samples obtained 64 respondents, measuring instrument data collection using questionnaire. Result: The result is if at SPSS Version 22 using 2x2 table with Chi-Square test with significance level table ? = 0,05. The result of bivariate relationship between age with the incidence of rupture of membranes early with P value = 0,024, the relationship between parity with the incidence of rupture of membrane early so that the value can P Value = 0.002 and the relationship of multiple pregnancy with premature rupture membrane in the mother of labor at RSUD Labuang Baji Makassar P Value = 0.001. Discussion: multiple pregnancy is one of the causes of premature rupture of the membranes, due to intense intra-uter pressure causing the membranes to thinned and ruptured. Conclusion: The conclusion in this study is the relationship between age, parity, multiple pregnancy to the incidence of premature rupture of membranes in maternity mothers at RSUD Labuang Baji in 2016 Makassar.